Guinea : Poverty Reduction Strategy Second Annual Progress Report. (IMF Staff Country Reports; Country Report, 2006)
This paper presents key findings of the Annual Progress Report (APR) on the Poverty Reduction Strategy Paper (PRSP) for Guinea. Conditions for implementing the Poverty Reduction Strategy were particularly difficult in 2004, and were marked by: persistent insecurity in the subregion; low levels of investment in priority sectors; and falling prices for mining output, in particular for bauxite, the country's main export. The outcomes achieved during fiscal year 2004 are a reflection of this constraining environment. Under the circumstances, no progress was made in reconciling the central government budget with the PRSP objectives.